The Furies: Violence and Terror in the French and Russian Revolutions - ARNO J. MAYER (Princeton University Press, 2013)
THIS BOOK, like any historical work, has a history, and it was crafted in a specific political and historiographic context. In 1987, I finished Why Did the Heavens Not Darken? and resumed work on the sequel to The Persistence of the Old Regime, which I had put aside to ponder and search into the Judeocide. But a turbulence in the surrounding political and intellectual atmosphere distracted me. I spent much time in France in 1987â€“90, the years of the rites of the bicentennial of the French Revolution, in which historians were prominent officiants. There was nothing exceptional about French historians, particularly the public intellectuals among them, playing their self-assigned roles. They had been doing so practically ever since 1789, taking three distinct positions: abjure and excoriate the Revolution, root and branch; redeem the â€œrevolution without a revolutionâ€ over against the radical revolution of the Terror; exalt and justify the Revolution, en bloc. There is something archetypal about these three positions: since 1917 they have defined the debates about the Russian Revolution, except that the third position eventually split in two over the question of the continuity or break between Lenin and Stalin. The â€œcrescendo of violenceâ€ (Jules Michelet) has been the single most important defining issue of the indomitable debate about the Great Revolution. For the bicentennial, French historians reenacted the tried and true battle between the prosecutors who blame one or more ideologically driven political leaders for the spiraling Furies, including the Terror, and the defenders who attribute them to the force of circumstance. Indeed, it seemed as if old polemical wine was being poured into new historiographic bottles. Presently, however, the bicentennial debate became singularly polemical and impassioned. In part this was so because as may be expected, it served as a screen for heated arguments about Franceâ€™s unmastered recent past. Had Vichy been the last stand of the counterrevolution dating from 1789, shielded by Nazi Germany? Had the French Communists, since the 1930s, been nothing but latter-day Jacobins, subservient to Soviet Russia? Not unrelated, the great historical ventilation was marked by the changing Zeitgeist which, in turn, it helped to shape. Because or in spite of the return of the tempered â€œleftâ€ to power in France in 1981, there was a vigorous resurgence of the far â€œrightâ€ and of traditional conservatism. This political and intellectual mutation coincided with the ascendancy of Ronald Reagan and Margaret Thatcher, along with their neoconservative clerks, in the United States and Great Britain, as well as with the breakthrough of glasnost and perestroika in East Central Europe and Russia. Simultaneously, academic Marxism was going out with the tide.